1987
DOI: 10.1007/bf01885178
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the colonoscopic localization of tumors: Continued value of the barium enema

Abstract: Six patients in whom errors of diagnosis and therapy occurred because of reliance on colonoscopic tumor localization are presented. Three of the patients required a second laparotomy for surgical resection of a tumor that was missed at the first exploration. While endoscopy is regarded as the diagnostic gold standard, there are problems in its use for colonoscopic localization. Reliance on distance measurements may be misleading. Anatomical variants can be confusing. For this reason, a preoperative barium enem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 9 publications
0
35
1
Order By: Relevance
“…In the majority of cases, inadequate localization is favoured by the variable length and mobility of the sigmoid colon as well as by the lack of anatomical and endoscopical marks to define the transition between the sigmoid and descending colon. Surprisingly, other paper report completely opposite data, no finding endoscopic errors when the tumors are located in the descending (18) or the sigmoid colon (2). Finally, the comment that, as in our series, a high number of endoscopic errors has been reported for cecal CRC (12).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…In the majority of cases, inadequate localization is favoured by the variable length and mobility of the sigmoid colon as well as by the lack of anatomical and endoscopical marks to define the transition between the sigmoid and descending colon. Surprisingly, other paper report completely opposite data, no finding endoscopic errors when the tumors are located in the descending (18) or the sigmoid colon (2). Finally, the comment that, as in our series, a high number of endoscopic errors has been reported for cecal CRC (12).…”
Section: Discussioncontrasting
confidence: 58%
“…Under certain circumstances, an error will not influence the surgical procedure (right hemicolectomy with a wrong diagnosis between cecum or ascending colon). However several publications have showed that a previous mistaken localization has been responsible of serious situations as resecting a colonic segment not containing the tumor (2,18,20). In all our cases, errors consisted in localizing CRC in the proximal or distal segment to its real surgical situation, and so initial surgical plan had to be modified in only one case, changing to open surgery and intraoperative colonoscopy performance was required in two patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Tumor localization techniques for early CRC are necessary, even in open surgery, because early cancer cannot be manually palpated in many cases due to shallow cancer invasion, small size and lack of visible serosal signs [36,37]. Furthermore, laparoscopic early CRC localization may be impossible without the use of localization tools, because tactile sensation is essentially lost laparoscop- ically.…”
Section: Discussionmentioning
confidence: 99%